EVALUASI KEBIJAKAN PENYUSUNAN STANDAR KOMPETENSI JABATAN STRUKTURAL - Ratminto Ratminto (Jurnal Manajemen Kepegawaian, 2007)
Competency is one of the most crucial factors in managing human resources, in order to produce the greatest value for the key stakeholders. This article critically reviews the policy of the Indonesian Government in formulating the competencies standard for the civil servant leaders. Key words: Competency, managerial skills and organizational competitiveness.